Chemical hole doping into large-area transition metal dichalcogenide monolayers using boron-based oxidant. (18th January 2018) - Matsuoka, Hirofumi; Kanahashi, Kaito; Tanaka, Naoki; Shoji, Yoshiaki; Li, Lain-Jong; Pu, Jiang; Ito, Hiroshi; Ohta, Hiromichi; Fukushima, Takanori; Takenobu, Taishi
Abstract: Hole carrier doping into single-crystalline transition metal dichalcogenide (TMDC) films can be achieved with various chemical reagents. However, large-area polycrystalline TMDC monolayers produced by a chemical vapor deposition (CVD) growth method have yet to be chemically doped. Here, we report that a salt of a two-coordinate boron cation, Mes2 B + (Mes: 2, 4, 6-trimethylphenyl group), with a chemically stable tetrakis(pentafluorophenyl)borate anion, [(C6 F5 )4 B] −, can serve as an efficient hole-doping reagent for large-area CVD-grown tungsten diselenide (WSe2 ) films. Upon doping, the sheet resistance of large-area polycrystalline WSe2 monolayers decreased from 90 GΩ/sq to 3.2 kΩ/sq.